Innovative technologies of water treatment for intensification of crop growth - Шевчук, Лілія Іванівна; Старчевський, Володимир Людвігович; Афтаназів, Іван Семенович; Коваль, Ірина Зеновіївна; Строган, Орися Іванівна (Technology audit and production reserves, 2013)
The article presents a new technology of water preparation for crops watering, based on the cavitational water treatment. The article describes the high-productive low frequency vibrational cavitator for cavitational water treatment, the results of experimental studies of the impact of activated cavitation of water on germination and growth of legumes and crops. We have confirmed positive effect of cavitational water treatment on the rate of germination and growth of crops, high efficiency of vibroresonance cavitational treatment as a mean of active restructurization of water to the state approximate to its monomolecular structure. It was determined that regardless of species of plants studied the rate of their growth when watering with cavitationally treated water significantly exceeds the growth rate when watering with regular water, and the difference in the rate of growth depends on a variety of crops and increases with increasing the duration of watering.